Pengaruh Penundaan Serum Segera dan 24 Jam terhadap Pemeriksaan Kadar Kolesterol di RSU Sinar Kasih Purwokerto - Alfiana Herawati; Oksita Asri Widyayanti; Cici Farhana Ambarwanty (Jurnal Medika Nusantara, 2025)
Cholesterol is a component of fat or lipids. Fat is a nutrient that the body actually needs, but if cholesterol levels are high it can cause disease. Cholesterol sufferers in Indonesia are quite high, namely 28% and 7.9% of cases cause cholesterol sufferers in the world to die from this disease. If treated too late, high cholesterol will actually endanger health and can even lead to death. Methods have been developed for examining total cholesterol in the blood in the laboratory, namely enzymatic methods such as Cholesterol Oxidase Deaminase Peroxidase Aminoantipyrine (CHOD-PAP). The aim of this study was to determine the difference in cholesterol levels between immediate serum examination and serum whose examination was postponed. The research was carried out experimentally using a Time Series Design. From the results of the examination of 16 samples, cholesterol levels were obtained based on the Paired Sample T-Test. From the calculation results, namely 0.000, it can be concluded that there is a difference in the results of checking cholesterol levels immediately and with a delay of 24 hours.